Identifying State Dependence in Brand Choice: Evidence from Hurricanes - Julia Levine; Stephan Seiler (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze structural state dependence in brand choice using variation from brand switching during stock-outs caused by hurricanes. We derive a simple test for structural state dependence based on the time-series of choice persistence for households affected by the stock-outs. Using data from the bottled water category, we show that demand increases substantially before hurricanes, causing households to purchase different brands. We find that purchase behavior reverts back to its pre-hurricane trajectory immediately after a hurricane and we are not able to reject the null hypothesis of no structural state dependence. By contrast, the common approach of estimating structural state dependence based on temporal price variation via a discrete choice model yields a positive effect using data for the same category. We argue that our approach is better suited to identify the causal impact of past choices because it requires fewer assumption and is based on more plausibly exogenous variation in brand switching due to stock-outs.
Keywords: C23; C51; L81; M31; 330; brand choice; brand loyalty; state dependence; preference heterogeneity